Vestibular Toxicity: Causes, Evaluation Protocols, Intervention, and Management - Gans, Richard E.; Rauterkus, Grant; Research Associate (Seminars in Hearing, 2019)
The loss of vestibular function, typically bilateral, due to chemical solvents and pharmacological agents is not rare and has been investigated and reported for many years. The successful treatment of bacterial infections and sepsis with IV antibiotics and cancer-fighting drugs like cisplatin makes the decision to use these life-saving drugs less of a debate, despite their potential deleterious effect on balance and equilibrium. The purpose of this article is to provide the reader with an overview of the more common substances found in industry and medicine which may decrease or permanently destroy peripheral and/or central vestibular function. A review of bedside and clinical evaluation protocols will be discussed as well as best practice intervention with balance retraining therapy. Finally, the role of the audiologist and opportunities for participation in an interdisciplinary approach to evaluation and management will be presented.
Keywords: vestibular; vestibulotoxic; balance retraining; fall-risk management